A Comparison of Facial Emotion Recognition in Patients with Temporal Lobe Epilepsy and Non-epileptics - Masjedi Arani, Abbas; Batebi, Sepideh; Dolatshahi, Behrooz; Azimian, Mojtaba (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Temporal lobe epilepsy (TLE) is related to the mesial temporal lobe structures such as the hippocampus, amygdala, and Parahippocampal gyrus. In patients with TLE, the amygdala complex is a component of the temporal lobe that is damaged. Previous studies on emotional processing have proven deficits due to amygdala damage in these patients. The present study compares the facial emotion recognition in patients with temporal lobe epilepsy and healthy controls. It was hypothesized that the TLE group have more dysfunctions than non- people with epilepsy. Methods: In this comparative study, 120 subjects, including 60 patients with a definite diagnosis of the temporal lobe and 60 non-epileptic individuals, were recruited using purposive sampling. The patient group was chosen from the Chamran hospital and Iranian Epilepsy Association, Tehran, Iran. The research data were collected by the Ekman computer test of facial emotion recognition. This test uses 36 images to measure the six basic emotions (i.e., happiness, disgust, anger, fear, sadness, and surprise); these images were adapted from the Ekman and Friesen series of images. The data were analyzed using multivariate analysis of variance by SPSS Statistics 19-IBM in two levels of response accuracy and reaction time in TLE patients and healthy individuals. Results: Data analysis showed a significant difference in the response accuracy of facial expressions of happiness, disgust, anger, fear, sadness, and surprise in patients with TLE (P < 0.01). Furthermore, recognizing emotions of fear, disgust, and anger in patients with TLE was more inadequate. When it came to the reaction time of emotion recognition, the TLE patients showed a higher functional impairment than the healthy group (P < 0.01). The reactions to fear and disgust were notably slower than other emotions. Conclusions: The results showed more inaccurate facial emotion recognition of fear, disgust, and anger inferred from facial expressions. Moreover, the reaction time response of facial emotion recognition for all six emotions was slower, compared to non-epileptics. Assessing the emotional recognition dysfunction through this measurement can facilitate recognizing the emotional deficiency regarding social communication in TLE patients. Psychological dysfunction can be a predictor of not a good response to the treatment, more frequency of seizures, and worse quality of life in these patients.